Influencer Marketing and Product Quality Shaping Customer Satisfaction via Purchase Decisions: Pemasaran Influencer dan Kualitas Produk Membentuk Kepuasan Pelanggan melalui Keputusan Pembelian - Hasan, Fahri Abu; Muzakir, Muzakir; Wahyuningsih, Wahyuningsih; Evrianti, Hesti (Universitas Muhammadiyah Sidoarjo, 2025)
General background: In the digital marketing era, brands increasingly rely on social media to influence consumer behavior. Specific background: Roti John Surabaya leverages influencer marketing to build brand awareness, while product quality remains a core determinant of customer loyalty. Knowledge gap: However, limited research addresses how these two factors jointly influence satisfaction through consumer decision-making. Aims: This study investigates the influence of influencer marketing and product quality on consumer satisfaction, with purchase decision as a mediating variable. Results: Using a quantitative approach and data from 120 respondents, analysis via Partial Least Squares Structural Equation Modeling (PLS-SEM) reveals that both influencer marketing and product quality significantly and positively impact purchase decisions and consumer satisfaction. Moreover, purchase decisions significantly mediate these relationships. Novelty: The integration of influencer marketing and product quality as dual predictors, examined through the mediating role of purchase decision, offers a comprehensive model not widely explored in the local F&B industry context. Implications: These findings underscore the strategic value of collaborating with influencers and continuously enhancing product quality to drive consumer satisfaction and purchasing behavior, providing practical insights for marketing optimization in competitive digital marketplaces. Highlights: Highlights the dual impact of influencers and product quality on satisfaction. Demonstrates purchase decision as a key mediating factor. Offers actionable insights for digital marketing practices. Keywords: Influencer Marketing, Product Quality, Purchase Decision, Consumer Satisfaction, Marketing Strategy